(untitled) (Anwer Khan Modern Medical College Journal, 2013)
In the era of information explosion, it is impossible for anyone to keep himself up-to-date with the literature by reading alone. Moreover there is vast amount of un-useful information added each day in the literature. Someone has to remain up-to-date with the valid and usable new information. Since its inception, journal club has been used as a useful meeting with the purposes of staying abreast of scientific publications and to judge their usability. In this article the concept of journal club and its practices were reviewed. The journal club has been proved to be a versatile program for its adaptable and multidirectional format to help the participants to develop many essential skills. It is now used as an academic program and is incorporated into curriculum in many institutes. Critical appraisal journal club models are most widely used to accomplish defined learning objectives. Evidence based journal club is one step ahead, through which practitioners judge the evidences and weigh its usability to bring a change in practice. Each institute should have defined journal club objectives for the development of students learning capability and also to develop and cultivate more skilled faculty. The practice of journal club can be adjusted and formatted according to the set goal of the organizing authority and the learning objectives of the participants. Anwer Khan Modern Medical College Journal Vol. 4, No. 2: July 2013, Pages 42-48 DOI: http://dx.doi.org/10.3329/akmmcj.v4i2.16942